High Prevalence of blaCTXM–1/IncI1-Iγ/ST3 Plasmids in Extended-Spectrum β-Lactamase-Producing Escherichia coli Isolates Collected From Domestic Animals in Guadeloupe (French West Indies) - Gruel, Gaëlle; Couvin, David; Guyomard-Rabenirina, Stéphanie; Arlet, Guillaume; Bambou, Jean-Christophe; Pot, Matthieu; Roy, Xavier; Talarmin, Antoine; Tressieres, Benoit; Ferdinand, Séverine; Breurec, Sébastien (Frontiers in Microbiology, 2022)
Extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) have been classified in the group of resistant bacteria of highest priority. We determined the prevalence of ESBL-E collected in feces from household and shelter pets in Guadeloupe (French West Indies). A single rectal swab was taken from 125 dogs and 60 cats between June and September 2019. The prevalence of fecal carriage of ESBL-E was 7.6% (14/185, 95% CI: 4.2-12.4), within the range observed worldwide. The only risk factor associated with a higher prevalence of ESBL-E rectal carriage was a stay in a shelter, suggesting that refuges could be hotspots for their acquisition. All but one (Klebsiella pneumoniae from a cat) were Escherichia coli. We noted the presence of a blaCTX–M–1/IncI1-Iγ/sequence type (ST3) plasmid in 11 ESBL-producing E. coli isolates belonging to ST328 (n = 6), ST155 (n = 4) and ST953 (n = 1). A blaCTX–M–15 gene was identified in the three remaining ESBL-E isolates. The blaCTX–M–1 and most of the antimicrobial resistance genes were present in a well-conserved large conjugative IncI1-Iγ/ST3 plasmid characterized by two accessory regions containing antibiotic resistance genes. The plasmid has been detected worldwide in E. coli isolates from humans and several animal species, such as food-producing animals, wild birds and pets, and from the environment. This study shows the potential role of pets as a reservoir of antimicrobial-resistant bacteria or genes for humans and underlines the importance of basic hygiene measures by owners of companion animals.